The selection of media for the accumulation of Bacillus anthracis Sterne 34F2 - Мачуський, О. В. (Scientific Progress & Innovations, 2012)
There were outlined the need of developing and introducing of new preparations for anthrax prevention. The nutrient media for accumulation of Bacillus anthracis Sterne 34F2 were selected. Also the main parameters of selected media had been displayed. In the accordance to the results of research we established the optimum dense media, which contain 100-120 mg% of amine nitrogen, has pH of 7,4 ± 0,2 and manufactured by Hottinger digest.